A Stubborn Fury How Writing Works in Elitist Britain - Hall, Gary (MEDIA : ART : WRITE : NOW, 2021)
Two fifths of Britain's leading people were educated privately: that's five times the amount as in the population as a whole, with almost a quarter graduating from Oxford or Cambridge. Eight private schools send more pupils to Oxbridge than the remaining 2894 state schools combined, making modern Britain one of the most unequal places in Europe. In A Stubborn Fury, Gary Hall offers a powerful and provocative look at the consequences of this inequality for English culture in particular. Focusing on the literary novel and the memoir, he investigates, in terms that are as insightful as they are irreverent, why so much writing in England is uncritically realist, humanist and anti-intellectual. Hall does so by playfully rewriting two of the most acclaimed contributions to these media genres of recent times. One is that of England's foremost avant-garde novelist Tom McCarthy, and the importance he attaches to European modernism and antihumanist theory. The other is that of the celebrated French memoirists Didier Eribon and Édouard Louis, and their attempt to reinvent the antihumanist philosophical tradition by producing a theory that speaks about class and intersectionality, yet generates the excitement of a Kendrick Lamar concert. Experimentally pirating McCarthy, Eribon and Louis, A Stubborn Fury addresses that most urgent of questions: what can be done about English literary culture's addiction to the worldview of privileged, middle-class white men, very much to the exclusion of more radically inventive writing, including that of working-class, BAME and LGBTQIAP+ authors?